PENERAPAN SANKSI PIDANA TERHADAP PEMILIK TEMPAT PROSTITUSI DI KECAMATAN SIATAS BARITA KOTA TARUTUNG - Maria Hose Sihombing; Mexsasai Indra; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Prostitution is a social phenomenon where women sell themselves doing sexual acts as a livelihood. In this definition clearly stated the existence of self-selling as a